Risk perception and practices towards fire safety among occupants of residential college in a higher learning institution - Chen, Pei Wen (2025)
Failure to prepare awareness of students on fire safety and prevention in residential college adequately poses a significant risk. This may result in various losses, not only in terms of safety, health and human lives, but also in the aspects of property, morale and intellectual properties. As risk perception relates closely to knowledge, attitude and practices (KAP), the purpose of this study was to identify the level of knowledge, attitude, and practices (KAP) and level of risk perception and the relationship between risk perception and practices towards fire safety among occupants of residential college in a higher learning institution by using quantitative method and convenience sampling. The questionnaire was first validated by two experts in the related field. The validated questionnaire was then distributed via face-to-face and online to 363 students who stayed in the residential colleges. This study found that the students have a high level of knowledge (m=3.90), attitude (m=4.51) and practices (m=4.16) towards fire safety but they have moderate level of risk perception (m=3.08) towards fire safety. Meanwhile, there is low significant correlation between risk perception and practices towards fire safety (r=0.189, p=0.000). Thus, through education and awareness about the fire risks in residential college and the significance of fire safety may lead to good practices towards fire safety among occupants in the residential college of a higher learning institution.